Una aproximación reflexiva a la crisis del multilateralismo frente al paradigma de la lucha contra el narcotráfico y el desarrollo sostenible: ¿la erradicación de cultivos ilícitos en Colombia y Perú como paradigma alternativo? ¿la erradicación de cultivos ilícitos en Colombia y Perú como paradigma alternativo? (2022)
This paper aims to analyze and reflect on the current crisis of multilateralism and its general principles of conduct —ideas, discourses and practices— which may represent a scenario of opportunities and threats to respond to the complexity of the world drug problem and the crisis of its dominant paradigm whose strategy, primarily military, represents an anachronistic worldview regarding security reduced to the prohibitionist approach. Likewise, there are debates on the dominant development paradigm, built on global agreements and their general principles of conduct —ideas— that have determined and constrained a multidimensional approach in the case of Colombia and Peru. In this way, the worldview has been determined by the dialectical vision of the internal world —harmony— and external —anarchy— according to the rationalist approaches which, from the critique of reflective approaches in International Relations, poses more than an explanation (causality), the understanding (interpretation) and coconstitution of reality and current phenomena, such as the world drug problem and development for the consolidation of alternative paradigms in Colombia and Peru.